Development of a power operated black pepper thresher - SUMA NAIR (Tavanur 1998 Kelappaji College of Agricultural Engineering and Technology)
conventional method of pepper threshing is by treading the pepper spikes under human feet. the pepper spikes are heaped on ground after harvest, and after a dya or two, are spread on floor or mats and trod upon. the berried get seperated from the stalks by the shearing action
Development of a power operated black pepper thresher